[18F]‐Fluorodeoxyglucose Positron Emission Tomography Standardized Uptake Value as a Predictor of Adjuvant Chemotherapy Benefits in Patients With Nasopharyngeal Carcinoma. (15th April 2015) - Hsieh, Te‐Chun; Hsieh, Ching Yun; Yang, Tse Yen; Chen, Tzu Ting; Lin, Chen Yuan; Lin, Ching‐Chan; Hua, Chung Hung; Chiu, Chang‐Fang; Yeh, Su‐Peng; Sher, Yuh Pyng
Abstract : Background: The role of adjuvant chemotherapy for the treatment of nasopharyngeal carcinoma (NPC) is controversial, and the identification of adequate predictive factors is warranted. Therefore, we aimed to investigate whether the mean standardized uptake value (SUV) measured on [ 18 F]‐fluorodeoxyglucose (FDG) positron emission tomography (PET) could predict the survival benefits for NPC patients that receive adjuvant chemotherapy. Materials and Methods: The data for 174 NPC patients who underwent PET/computed tomography before chemoradiation between January 2004 and January 2012 were reviewed. The SUV75% was recorded for primary tumors. All patients received intensity‐modulated radiotherapy and cisplatin‐based chemotherapy. Adjuvant chemotherapy consisted of 3 cycles of 75 mg/m 2 cisplatin and 1, 000 mg/m 2 fluorouracil for 4 days. Results: The optimal cutoff value was 8.35 for SUV75%, with 112 (64.4%) patients having lower SUV75% and 62 (35.6%) having higher SUV75% . Patients with lower SUV75% had significantly better 5‐year overall survival (OS) and distant metastasis‐free survival. Multivariate analysis revealed that tumor stage, SUV75%, and adjuvant chemotherapy were significant prognostic factors for OS. Patients with higher SUV75% had significantly higher 5‐year OS rates with adjuvant chemotherapy than without adjuvant chemotherapy (84.3% vs. 32.4%, respectively; p < .001). However, in the lower SUV75% group, no differences in 5‐year OS were observed between patients who received and those who did not receive adjuvant chemotherapy (92.4% vs. 93.3%, respectively; p = .682). Conclusion: The SUV75% on FDG PET for primary tumors could successfully identify NPC patients who may benefit from adjuvant chemotherapy. Abstract : This retrospective study revealed that the standardized uptake value (SUV) of [18F]‐fluoro‐2‐deoxy‐glucose positron emission tomography (FDG PET) was a significant prognostic factor, predicting which patients with locally advanced nasopharyngeal carcinoma (NPC) would benefit from adjuvant chemotherapy. The SUV of FDG PET deserves further investigation to evaluate whether it can be a novel marker for tailoring personalized therapy for NPC patients. Abstract : 摘要 背景。 辅助化疗在鼻咽癌(NPC)治疗中的作用是有争议的, 并且识别足够的预测因素是有必要的。因此, 我们的目的是研究测得的[ 18 F]‐氟脱氧葡萄糖(FDG)正电子发射断层扫描(PET)平均标准摄取值(SUV)是否可以为接受辅助化疗的鼻咽癌患者预测生存获益。 材料和方法。 对 174 例在 2004 年 1 月至 2012 年 1 月期间于化放疗前接受 PET/计算机断层扫描的NPC患者数据进行了审核。对原发肿瘤记录 SUV75% 。所有患者均接受调强放疗和基于顺铂的化疗。辅助化疗为顺铂75mg/m 2 及氟尿嘧啶1 000 mg/m 2, 每4 天一个疗程, 共3个疗程 。 结果。 SUV75% 的最佳临界值是 8.35, 其中 112例(64.4%)患者有较低的 SUV75%, 62例(35.6%)患者有较高的 SUV75% 。 较低 SUV75% 的患者具有显著较好的 5 年总生存(OS)和无远处转移生存率。多因素分析发现, 肿瘤分期、SUV75% 以及辅助化疗是 OS 的显著预后因素。接受辅助化疗且具有较高 SUV75% 的患者明显比不接受辅助化疗的患者有更高的 5 年 OS 率(分别为 84.3% 和 32.4% ; p < 0.001)。但是, 在较低的 SUV75% 组, 在接受和不接受辅助化疗的患者之间没有观察到 5 年 OS 率的差异(分别为 92.4% 和 93.3% ; p = 0.682)。 结论。 原发性肿瘤 FDG PET 的 SUV75% 可以成功识别可能获益于辅助化疗的NPC患者。 The Oncologist 2015;20:539–545